PENGETAHUAN DAN SIKAP IBU YANG MEMPUNYAI ANAK BALITA TENTANG PENYAKIT CAMPAK - Reni Rohaniah; Nenden Nur Asriyani Maryam; Sukmawati (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
In Garut regency in 2016 has occurred 323 cases of measles extraordinary events (KLB) with 32people died and the highest number of death is in Kersamenak Community Helath Center as manyas 48 cases. An effort to prevent measles is by giving immunizations. The scope of immunizationcan be influenced by the knowledge and attitudes of mothers about measles immunization. Thepurpose of this study was to determine the description of knowledge and attitudes of mothers whohave toddlers about measles in the Kersamenak Community Health Center in Garut Regency. Thestudy design used quantitative descriptive. The population in this study was mothers who hadchildren under five in the working area of Kersamenak Community Health Center as many as 231mothers. The sample was taken by purposive sampling technique, the number of samples as manyas 146 mothers who have toddlers. The instrument used was made by researcher with a valid test rtable ? 0.514 and a reliable Cronsbach alpha test 0.944. Analysis of the data was univariate. Theresults showed that most of mothers has good knowledge as many as 100 people (68.5%) andalmost half of th mothers have favorable attitude as many as 74 people (50.7%). It can beconcluded from this research that the mother's knowledge is sufficient because they understandsthe meaning of measles, how to be infected by measles, signs of measles, complications of measles,prevention of measles, and care for measles. Attitude of the mothers was favorable due to thecognitive, affective and conative attitude of most mothers strongly agree with environmentalhygiene, measles symptoms and information on the benefits of measles immunization. It is expectedthat the Community Health Center can provide more intensive information to the public aboutmeasles.